Pengembangan Aplikasi Media Pembelajaran Matematika Pecahan Berbasis Android Untuk Siswa Kelas 5 SD dengan Metode Gamifikasi - Dwiki Kurniawan; Triana Harmini; Miftahuddin Fahmi (LPPM Universitas Putera Batam, 2025)
Mathematics learning, especially the topic of fractions, is often a challenge for 5th-grade students. An Android-based mathematics learning Application with gamification elements was developed to address the low interest of these students in the topic of fractions. This research aims to develop a gamified Android-based mathematics learning Application for the topic of fractions. The development methodused the Waterfall Software Development Life Cycle (SDLC) model, which includes the stages of requirements analysis, design, implementation, testing, and maintenance. The Application was designed with the integration of gamification features such as levels and challenges to enhance student motivation and understanding. The Application was tested through five stages: black box testing, compatibilitytesting, media expert testing, material expert testing, and user testing. The results of the black box test showed that all features functioned as planned. The functionality test results indicated that the Application can run properly on all devices with at least Android version 11. The media expert testing showed an average of 100%, and the material expert testing also showed an average of 100%. User testing conducted on 20 5 th grade students at MI Ma’arif surodikraman, Ponorogo, showed a very positive outcome. Based on a 1 to 5 rating scale, the average percentage of user satisfaction reached 90.1%, indicating a high level of acceptance. These results show that the Application functions well and is suitable for use.